Learning outcomes in external programme reviews: a case study from Bahrain. - Alamansoori, Wafa, Abdulrahman (The IIE., 2012)
This paper considers the role that learning outcomes play in the programme reviews conducted by the Higher Education Review Unit (HERU) of the Quality Assurance Authority for Education & Training (QAAET) in the Kingdom of Bahrain. The findings of the 12 bachelor programmes reviewed in the field of Business Administration reveal that almost all of those programmes have developed programme intended learning outcomes (ILOs). This, in most cases, is the result of the programme review framework developed and used by the HERU of the QAAET to review the programmes offered by higher education institutions operating in the Kingdom of Bahrain. There is evidence that the conducting of programme reviews has started a paradigm shift, moving programmes from an input-based approach towards an outcome-based approach. An outcome-based approach to programme design, delivery, assessment and evaluation will inevitably be of more significance as the Kingdom develops its National Qualification Framework, which is due to be implemented by the year 2014.
Keywords: Learning outcomes; Quality assurance; Programme review; Programme design; Programme review